Introduction: Mass Incarceration and Masculinity Through a Black Feminist Lens - Annette Ruth Appell; Adrienne D. Davis (Washington University Journal of Law & Policy, 2011)
Mass incarceration is one of the biggest obstacles to social justice and democratic equality in the United States. This nation leads the world in imprisonment. As Angela Davis contended, the “prison industrial complex is much more than the sum of all the jails and prisons in this country. It is a set of symbiotic relationships among correctional communities, transnational corporations, media conglomerates, guards’ unions, and legislative and court agendas.” Other developed states use social welfare policy to develop citizens’ capabilities, which increase their employment and life prospects. In stark contrast, the United States has evolved a fairly permanent underclass, which does not have access to the basic capabilities necessary to enjoy even a working-class existence. In addition, faced with the choice to classify the 1980s rise in drug addiction and expansion in illegal drug markets as either a public health or criminal crisis, the United States consistently opted for the latter. Understood in this light, the solution was clear and immediate: incarceration. This policy was part and parcel of the emergence of the prison industrial complex, which has transformed the American political economy. Much noted are the racial aspects and effects of mass incarceration, which has decimated communities of color across class and region. For this intellectual inquiry, we chose black feminism as our lens. We decided to approach this phenomenon through a gendered lens for several reasons. First, mass incarceration has deeply gendered effects that cannot be understood as purely racial products. It affects men of color as men, and not just as racialized beings. Second, as several of the papers emphasize, mass incarceration has had acute effects on families that black feminist thought is particularly well suited to address. Third, mass incarceration has introduced new forms of sexuality, both risks and desires that require a thick understanding of identity and intimacy. Finally, black feminism is particularly adept at prosecuting the gendered dimensions of power and state violence.
Keywords: Black feminism; Prisons -- mass incarceration; Masculinity; Race; Sexuality